Continuous cardiac output measured with a Swan‐Ganz catheter reacts too slowly in animal experiments with sudden circulatory failure. Issue 3 (6th June 2022) - Magnúsdóttir, Sigríður Olga; Simonsen, Carsten; Rasmussen, Bodil Steen; Lund, Peter Enemark; Kjærgaard, Benedict
Abstract: Background: In many animal experiments, it is vital to detect sudden changes in cardiac output (CO). This porcine study compared CO that was measured with a Swan‐Ganz pulmonary catheter with the gold standard (which was a transit‐time flow probe around the pulmonary artery) during interventions that caused hemodynamic instability. Methods: In one series, 7 pigs were exposed to sudden changes in CO. In another series, 9 pigs experienced more prolonged changes in CO. All the pigs had a Swan‐Ganz catheter placed into the pulmonary artery and a flow probe around the pulmonary artery. Adrenaline infusion and controlled hemorrhage were used to increase and decrease CO, respectively. The measurements of CO before and after each intervention were compared for correlation, agreement, and the time delay that it took each method to detect at least a 30% change in CO. A Bland–Altman test was used to identify correlations and agreements between the methods. Results: In the first series, there was a delay of 5–7 min for the Swan Ganz catheter to register a 30% change in cardiac output, compared with the flow probe. However, during prolonged changes in CO in the second series, there was a good correlation between the 2 methods. Mixed venous oxygen saturation reacted faster to changes than did CO; both were measured via the Swan‐Ganz catheter. Conclusions: In many animal studies, the use of Swan‐Ganz catheters is suitable; however, in experiments with sudden hemodynamic instability, the flow probe is the most advantageous method for measuring CO. Abstract : The abrupt decrease in cardiac output (CO) over a short period of time with the measured values for the flow probe (FP), the Swan‐Ganz catheter (SG), and the mixed venous oxygenation (SvO2).